Dorsal intercostal artery flap: a reliable option for coverage of myelomeningocele defects: a case series - Khan, Majid; Sher, Faisal; Taimoor, Muhammad; Shamim, Muhammad Shahzad; Shaikh, Safdar Ali (Journal of the Pakistan Medical Association, 2024)
Meningomyelocele is a common congenital condition and its reconstruction poses a challenge for surgeons. The dorsal intercostal artery (DICA) flap offers a one-stage tension-free closure with adequate results. This study, spanning from January 2019 to September 2022, analyses the outcome of nine DICA flaps for meningomyelocele reconstruction, where the average size of the DICA flap was 6.8 x 4.6 cm for an average defect of 6.33 x 4 cm. Notably, no post-operative blood transfusion was required, nor any complications occurred except for one patient’s septic shock-related death. Two had post-operative cerebrospinal fluid (CSF) leak, repaired primarily with one requiring VP shunt. Based on our experience, the DICA flap, with its consistent anatomy, is a reliable option for the reconstruction of meningomyelocele defects. Keywords: Dorsal intercostal artery flap (DICA), Meningomyelocele, Neural tube defects, Reconstructive surgery, Fasciocutaneous flap.